2015
DOI: 10.1038/srep18432
|View full text |Cite
|
Sign up to set email alerts
|

Condensation and dissolution of nematic droplets in dispersions of colloidal rods with thermo–sensitive depletants

Abstract: Nematic droplets are droplets composed of elongated molecules that tend to point in the same direction but do not have any positional order. Such droplets are well known to adopt a spindle shape called tactoid. How such droplets condensate or melt and how the orientational symmetry is broken remains however unclear. Here we use a colloidal system composed of filamentous viruses as model rod–like colloids and pnipam microgel particles to induce thermo–sensitive depletion attraction between the rods. Microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 62 publications
5
30
0
Order By: Relevance
“…The effective attraction between the rods is then controlled externally by temperature. As temperature decreases, the microgel particle swell which increases both the range and the depth of the attraction [121]. Navigating the phase diagram in a continuous way, Modlińska et two viruses s interaction p depletion int with net line the fd as a h [11,33].Dot a correspond t rods with an attractive po modeled by radius (RAO= the potentia this approxim Influence of the depletant dextran (Mw =500 000 g/mol, radius of gyration Rg =17.6nm, concentration Dext) on an aqueous dispersion of fd-wt at a concentration cv [111].…”
Section: Nematic Dropletsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective attraction between the rods is then controlled externally by temperature. As temperature decreases, the microgel particle swell which increases both the range and the depth of the attraction [121]. Navigating the phase diagram in a continuous way, Modlińska et two viruses s interaction p depletion int with net line the fd as a h [11,33].Dot a correspond t rods with an attractive po modeled by radius (RAO= the potentia this approxim Influence of the depletant dextran (Mw =500 000 g/mol, radius of gyration Rg =17.6nm, concentration Dext) on an aqueous dispersion of fd-wt at a concentration cv [111].…”
Section: Nematic Dropletsmentioning
confidence: 99%
“…T 2 is the temperature that separates the isotropic droplets regimes from the tactoids regime. [121]. (a) Phase contrast images of a suspension of M13K07 viruses at cv = 1mg/mL mixed with pnipam microgel particles at cP = 30mg/mL.…”
Section: Nematic Dropletsmentioning
confidence: 99%
“…These nematic droplets have characteristic shapes that have already been the subject of several theoretical studies [2][3][4][5][6][7][8] and experiments on systems such as vanadium pentoxide (V 2 O 5 ) [2,9], carbon nanotubes [10,11], rodlike viruses [12,13], F-actin in cells [14], chromonic liquid crystals [15], and cellulose nano-crystals [16][17][18]. These investigations showed that the typical tactoid shapes, for example the so-called spindle-like shape with a bipolar director field (see the right inset in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…When a droplet is formed from a nematic phase, either by phase separation or by fabrication, then the shape of this droplet and the director field are set by the competition between the elastic properties of the nematic liquid crystalline phase, the interfacial tension and the anchoring conditions of the mesogens that constitute the nematic phase [1,2]. Dispersions of colloidal rods often form droplets with a spindle-like shape during phase separation, the so-called tactoids, contrary to thermo-tropic liquid crystals that form spherical droplets [1,[3][4][5][6][7][8][9][10][11][12]. This is due to the fact that rods tend to align parallel to any wall, thus increasing the freely available volume [13].…”
Section: Introductionmentioning
confidence: 99%
“…Up to recently, no clear evidence of a twisted bipolar was found in tactoids of chiral nematic colloidal rods, such as the well-studied fd virus [12,29], despite of the chiral strength K t that drives the twisting. For the chiral amyloids discussed above, however, an additional cascade of transitions was observed from a bipolar to an uniaxial cholesteric to a radial cholesteric director field, forming, respectively, striped and ring patterns as the size of the droplets increased [10,11].…”
Section: Introductionmentioning
confidence: 99%